Design of a CMOS integrated on-chip oscilloscope for spin wave characterization - Egel E; Meier C; Csaba György; Gamm SBV (AIP ADVANCES, 2017)
Spin waves can perform some optically-inspired computing algorithms, e.g. the Fourier transform, directly than it is done with the CMOS logic. This article describes a new approach for on-chip characterization of spin wave based devices. The read-out circuitry for the spin waves is simulated with 65-nm CMOS technology models. Commonly used circuits for Radio Frequency (RF) receivers are implemented to detect a sinusoidal ultra-wideband (5-50 GHz) signal with an amplitude of at least 15 mu V picked up by a loop antenna. First, the RF signal is amplified by a Low Noise Amplifier (LNA). Then, it is down-converted by a mixer to Intermediate Frequency (IF). Finally, an Operational Amplifier (OpAmp) brings the IF signal to higher voltages (50-300 mV). The estimated power consumption and the required area of the readout circuit is approximately 55.5 mW and 0.168 mm(2), respectively. The proposed On-Chip Oscilloscope (OCO) is highly suitable for on-chip spin wave characterization regarding the frequency, amplitude change and phase information. It offers an integrated low power alternative to current spin wave detecting systems. (C) 2017 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).